High throughput screening for food safety assessment : biosensor technologies, hyperspectral imaging and practical applications - Bhunia, Arun K.; Kim, Moon S.; Taitt, Chris R. (Woodhead Publishing in food science, technology, and nutrition ;, 2015)
Recent advances in array-based detectors and imaging technologies have provided high throughput systems that can operate within a substantially reduced timeframe and other techniques that can detect multiple contaminants at one time. These technologies are revolutionary in terms of food safety assessment in manufacturing, and will also have a significant impact on areas such as public health and food defence. This book summarizes the latest research and applications of sensor technologies for online and high throughput screening of food. The book first introduces high throughput screening.